Synthesis and Characterization of Graphene like Carbon Nanosheet: Interaction with some Drug Molecules and Anticancer Activity. Issue 12 (27th April 2017) - Chattopadhyay, Asoke P.; Mandal, Prasenjit; Sarkar, Rajkumar; Samadder, Asmita; Khuda‐Bukhsh, Anisur R.; Yadav, Priya; Sarkar, Keka
Abstract: Graphene‐like carbon nano‐sheets are prepared from dextrin, with cetyltrimethyl ammonium bromide (CTAB) as stabiliser, by the action of concentrated sulfuric acid. Oxidation of such sheets produce graphene oxide (GO) like material. These are characterized in the usual manner and their photophysical properties are explored. Binding of certain drug molecules with carbon nano‐sheet is investigated fluorimetrically. Finally, action of carbon nano‐sheets on normal and cancer cell lines revealed that the sheets have no effect on normal cells, but induce apoptosis on cancer cells. Also, these carbon nano‐sheets behave very similar to reduced graphene oxide platelets. Abstract : Graphene‐like carbon nanosheets (CNS) are prepared from dextrin, with CTAB, a common surfactant, as stabiliser, by conc. sulfuric acid. CNS are like reduced GO (rGO), and their oxidation produces graphene oxide (GO) like material. These are characterized as usual and their photophysical properties observed. Binding of drug molecules e. g. curcumin, artemisinin, pentamidin etc. with the CNS is investigated fluorimetrically. Finally, action of CNS on normal and cancer cell lines revealed that CNS have no effect on normal cells, but induce apoptosis on cancer cells. Such action of CNS very similar to that of GO on same or similar cells.